Expression and purification of active, stabilized trimethyllysine hydroxylase - Kazaks, Andris; Makrecka-Kuka, Marina; Kuka, Janis; Voronkova, Tatyana; Akopjana, Inara; Grinberga, Solveiga; Pugovics, Osvalds; Tars, Kaspars (Protein expression and purification, 2014)
•TMLH expressed in E. coli either alone, or as MBP fusion is mainly insoluble.•Co-expression of MBP–TMLH with chaperonins GroES/EL markedly improves solubility.•Purified MBP–TMLH is stable and functionally active. Trimethyllysine hydroxylase (TMLH) catalyses the first step in carnitine biosynthesis – the conversion of N6,N6,N6-trimethyl-l-lysine to 3-hydroxy-N6,N6,N6-trimethyl-l-lysine. By changing carnitine availability it is possible to optimise cardiac energy metabolism, that is beneficial under certain ischemic conditions. Previous efforts have been devoted towards the inhibition of gamma-butyrobetaine dioxygenase, which catalyses the last step in carnitine biosynthesis. However, the effects of TMLH activity regulation are currently unexplored. To facilitate the development of specific ligands of TMLH, large quantities of recombinant protein are necessary for downstream binding and structural studies. Here, we describe an efficient system for expressing and purifying active and stable TMLH as a maltose-binding protein fusion in Escherichiacoli.